O episódio de Dido na Eneida: entre épica e tragédia - Teixeira, Cláudia (2012)
Dido’s episode in Virgil’s Aeneid thematises tragic elements in close relationship with the epic framework underlying the work. This article intends to inquire whether, in the context of the relationship of such elements, the queen’s fall represents the development of a tragic plot or of a frustrated epic plot.